Educational psychology in higher education: Current scene in Portugal - Bisinoto, Cynthia (2014)
Facing the challenges brought by Higher Education growth, the Higher Education Institutions (HEIs) created the Psychological Support Services. They seek to help the adaptation to the university setting, enhancing the overall students´ development and their integration in the labor market. This qualitative research studies the structure of the Psychological Support Services in HEIs of Portugal and the main activities developed by educational psychologists. Interviews were conducted with eight services and showed that all services are designed for students. Although the most frequent activity is the students' psychological consultation, educational psychologists also develop a variety of interventions: skill development programs, support to students with special needs, and mentoring programs to welcome new students. Traditionally the services were oriented by an individual intervention and in response to the students' problem. Nowadays they are working with other agents and in a preventive way. Actions directed to educational projects and the institutional evaluation could promote a qualitative change in services.